TMJ Ankylosis in Children: A Case Report and Literature Review - Abdouldaim Ukwas; Mahmoud Elshik; Mohammed Elbialy (Case Reports in Dentistry)
Temporomandibular joint (TMJ) ankylosis is a serious disabling condition characterized by fusion of the mandibular condyle with the glenoid fossa, disc, and/or eminence, resulting in severely restricted mouth opening and significantly reduced mandibular movements. The condition often has a deteriorating effect on the patient’s daily functions such as speech, chewing, breathing, and oral hygiene as well as their wellbeing and quality of life. Furthermore, childhood TMJ ankylosis frequently has a detrimental impact on the facial growth resulting in facial asymmetry, micrognathia, and/or class II malocclusion with posterior or anterior open bite. Trauma is the main cause of TMJ ankylosis, but the condition can also occur as a result of surgery, local or systemic infections, or systemic disease. Surgery is the mainstay of treatment, and several approaches have been applied, including gap arthroplasty (GA), interpositional gap arthroplasty (IGA), reconstruction arthroplasty (RA), or distraction osteogenesis (DO). The aim of this article is to present a post-traumatic TMJ ankylosis case in a 5-year-old male child who was treated with resection and simultaneous costochondral grafting and to provide a succinct update of literature.